From Islamist to Muslim democrat: the present phenomenon of Muslim politics in Malaysia - Mohd Izani Mohd Zain, (Universiti Kebangsaan Malaysia, 2014)
The Muslim political rivalry in democracy has triggered the birth of two groups; Islamist and Muslim Democrat. The two groups are competing by using a different approach in getting the support of the people. The Islamist group is championing its Islamic State agenda and the implementation of Shari`a as a political ambition within the framework of democracy while the Muslim Democrat recognises democracy and freedom as the basis of their struggle. Due to a greater development in democracy and a more open political rivalry, the Islamist group that was initially strongly backed by their rigid ideology and approach, has decided to change for a more moderate approach. This can be seen through their political strategy that emphasises on universal issues such as democracy, justice and good governance without rhetorical expressions of Islam and Shari`a. This change from Islamist to that of Muslim Democrat is an exciting development for it shows the transition path and direction of Muslim politics in Malaysia. This paper examines the latest development of the Islamist group, i.e. PAS in political rivalry in Malaysia, particularly in the recent General Election in 2013. This article reveals that due to the changing political landscape and democratization, the Islamist has pragmatically moderated their stance to gain more supports and it has embarked on a new landscape for Muslim political rivalry in Malaysia. Although PAS’s new approach to transform its approach to be more open and democratic is still questionable, this study believes that the participation of the party in democracy is no longer just for the sake of election, on the other hand it should recognise democracy as a political culture that emphasizes justice, freedom and good governance.